ANALISIS KEY SUCCESS FACTORS UNTUK MEMPERTAHANKAN KEUNGGULAN BERSAING PADA PT ASTRA INTERNASIONAL - Rachmawati, Jenny Indriawan (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to identify and to analyze the key success factors in order to reach the competitiveadvantage at PT Astra International Surabaya. The research method which is performed in this research byusing the qualitative method in order to find out and to analyze the key success factors in order to achieve thecompetitive advantage. The data analysis technique which is applied in this research is the descriptive analysisqualitative approach which is conducted by expressing definitions and explanation as well as making comparisonof the data which is achieved from the research to the existing theories. Based on the results of the analysis anddiscussion which are related to the key success factors in achieving competitive advantage at PT AstraInternational Surabaya, it can be concluded that the more coordinated a company strategy it will be more easierto maintain a competitive advantage so it can improve performance, lead the car market and reach the profitwhich are expected by the company.Keywords: Key Success Factors, Competitive Advantage.